2017
DOI: 10.1123/jpah.2016-0572
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment and Behavioral Intention Predict Organized Youth Sport Participation and Dropout

Abstract: Findings support the use of enjoyment and behavioral intentions as indicators of sport participation/dropout behavior and may aid the development of interventions aimed at preventing future dropout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
74
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 30 publications
11
74
0
6
Order By: Relevance
“…The first theme, Enjoyment, is in line with past research that has shown ones' positive satisfaction is a key motivational resource for retention in sport participation (Crane & Temple, 2015;Gardner et al, 2017). Also, according to the results of qualitative data, a majority of athletes highlighted meeting new people from different countries as a positive experience in CYG.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The first theme, Enjoyment, is in line with past research that has shown ones' positive satisfaction is a key motivational resource for retention in sport participation (Crane & Temple, 2015;Gardner et al, 2017). Also, according to the results of qualitative data, a majority of athletes highlighted meeting new people from different countries as a positive experience in CYG.…”
Section: Discussionsupporting
confidence: 76%
“…Sport psychology research has denoted that the positive feelings a person ascertains from their sport experience are important factors in determining their retention (Crane & Temple, 2015;Gardner, Magee, & Vella, 2017). Specifically, the level of satisfaction a person experiences in sport contributes to their attitude toward continuation (Crane & Temple, 2015;Gardner et al, 2017;Ryan & Deci, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies expanding the HMIEM, considering the prediction of one outcome to another (eg, enjoyment → intention), are uncommon, 9 and to the best of our knowledge, no study has measured and added observable outcomes, such as behavior persistence on the model sequence. This gap in the literature regarding the effect of enjoyment on behavioral intentions and behavioral performance has been previously reported 21 and highlighted by systematic reviews, 22,23 showing the particular importance of enjoyment and intentions on behavior enactment.…”
Section: Present Researchmentioning
confidence: 91%
“…Focusing on the effects that these variables have on young athletes, it was found that those who receive greater social support from their team or have higher levels of sports competence and autonomy have lower levels of burnout and higher levels of intrinsic motivation (DeFreese and Smith, 2013;Rottensteiner et al, 2015;Jowett et al, 2016). On the other hand, the absence of fun or the establishment of ego goals is closely related to the presence of burnout symptoms, as well as to sport dropout (Gardner et al, 2017;Sorkkila et al, 2018).…”
Section: Introductionmentioning
confidence: 99%